ANALISIS PENGARUH INOVASI PRODUK, KOMUNIKASI PEMASARAN DAN KUALITAS PRODUK TERHADAP CITRA MEREK DAN KEPERCAYAAN MEREK - Parri Sujodi Simbolon; I Made Sukresna (JURNAL STUDI MANAJEMEN ORGANISASI, 2021)
Gudang Garam is a leading clove cigarette producer which is identical to Indonesia, which is one of the main centers of spice trade in the world. Since 1989 to 2006, PT Gudang Garam Tbk (GGRM) had dominated the market with a share of around 28% to 47%. But since the first quarter of 2007, PT HM Sampoerna Tbk (HMSP), with the support of Philip Morris, takled Gudang Garam down and dominated the national cigarette industry. This study aims to analyze the effect of product innovation, marketing communication and product quality on brand image and brand trust in of Gudang Garam cigarettes. The variables used in this study are product innovation, marketing communication and product quality as independent variables, brand trust as an intervening variable and brand image as the dependent variable. The population used in this study is Gudang Garam branded cigarette consumers in the city of Semarang. The numbers of samples used were 200 respondents. This research uses Structural Equation Modeling (SEM) analytical technique using AMOS 23 analysis application and also assisted with SPSS analysis. The results of this study show that there is an interrelated connection among product innovation, marketing communication, and product quality towards brand image and brand trust., product quality has a positive and significant effect on brand image and brand trust and brand trust has a positive influence and significant towards brand image